Índice de sustentabilidade empresarial e retorno ao acionista: um estudo de evento - Dias, Edson Aparecido (2008)
There has been a lot of debate about Sustainability into the organizations recently. Some theorists state the organization should consider in their strategies elements that include the interest of the different stakeholders. This theoretical chain considers that economics, social and environmental systems are integrated, and so the organizations can t implement strategies which consider just one dimension. Other chain affirms the organizations should maximize the long term value and concentrate their efforts and investments on production and competitiveness, so they need to focus in only one objective, which is the long term value maximization of the firm, in this way, according this theory social welfare will be also maximized. In this complex context, sustainability indexes were created worldwide. These indexes in general, evaluate several dimensions and relations between the organization and society, environment and equity holders. In Brazil, was created in 2005 the sustainability index, ISE. Annually the BOVESPA announces to the market the new ISE Group, in which is included the companies that submit voluntarily, the answers to a wide survey about their sustainability practices. The inclusion on such group indicates the companies were evaluated according the rules of BOVESPA s sustainability rules. There are several discussions, if the organizations that make part of ISE group or similar, can capture abnormal returns to their shareholders, and if investments done in sustainability receive special attention by capital markets. This study investigates, using the event study methodology, if the announcement of being part of ISE group, creates value to shareholders. As event period was defined -15 to 120 days from announcement date, and in this period were created several event windows. In this research, the methodology is applied in two different ways: first; comparing the ISE group companies with a traditional Brazilian market index, the Ibovespa; second is the comparison with companies that have most part of their revenues from activities and products categorized in the same sector class (according BOVESPA) as the ISE ones, called in this study as control group. The results indicate the companies included in the ISE group do not capture Cumulated Abnormal Returns (CAR), when compared with the index market, in any event window. Anyhow, there were not found results that infer about lost of value, due the ISE announcement to the firm. By the other way, the results indicated that ISE companies can capture cumulated abnormal returns with statistically significant levels, when compared with the control group, in windows close to the announcement day. These results could be used to support manager s processes of decision, for establishing policies regarding sustainability of organizations.